A Companion to Shakespeare's Works : Volume 1, The Tragedies. - Dutton, Richard (Blackwell companions to literature and culture., 2007)
The four-volume Companion to Shakespeare's Works, compiled as a single entity, offers a uniquely comprehensive snapshot of current Shakespeare criticism. This volume looks at Shakespeares tragedies.:.; Contains original essays on every Shakespearean tragedy from Titus Andronicus to Coriolanus.; Includes thirteen additional essays on such topics as Shakespeare's Roman tragedies, Shakespeare's tragedies on film, Shakespeare's tragedies of love, Hamlet in performance, and tragic emotion in Shakespeare.; Brings together new essays from a diverse, international group of scholars.; Complements Davi.